Blockchain acceptance and deployment: A catalyst for microeconomic stability with financial performance as a mediator - Putra P, Komang Widhya Sedana (Universitas Ahmad Dahlan, 2025)
The study assesses blockchain technology acceptance and diffusion with its resultant impact on microeconomic stability, mediated by financial performance. It highlights blockchain's role in enhancing efficiency, transparency, and security, potentially increasing microeconomic stability. The questionnaires were administered to SME managers on the Indodax exchange platform, grounded in the Technology Acceptance Model (TAM) framework and Trade-off theory. Partial Least Squares Structural Equation Modeling (PLS-SEM) used for data analysis to establish the relationship among blockchain acceptance and deployment, financial performance, and microeconomic stability. The results indicated a significant positive consequence of blockchain acceptance and deployment on the financial performance of companies. Financial performance acted as the mediating variable between blockchain acceptance and deployment and microeconomic stability. Managerial implications show that commitment from top leadership, risk management, and stakeholder engagement are crucial for sustainable blockchain acceptance and deployment. This work elaborates on how blockchain technology can strengthen microeconomic stability and improve financial performance by providing practical guidance for organizations. However, it excludes considerations of operational costs, license fees, government regulations, cold chain management integration, demographic diversity, geographic expansion, alternative variables, sustainability, Bitcoin mining, longitudinal data collection, theoretical advantages for SMEs, supply chain efficiency, specific fintech subsectors, interoperability, scalability, macroeconomic variables, or ownership identity impacts. Despite these gaps, this research remains instrumental by providing foundational insights into the beneficial impacts of blockchain technology on financial performance and microeconomic stability, highlighting key areas for future investigation and guiding practice for current and potential adopters.